Effect of sorbent weight on H₂S removal by biochar and hydrogel biochar derived from rice husk: article / Amirul Rahman Mohd Nor and Azil Bahari Alias - Mohd Nor, Amirul Rahman; Alias, Azil Bahari (2018)
Biochar has received great attention recently as it has the potential to be alternative absorbent beside the long existence, activated carbon. In this study, biochar was produced from rice husk by slow pyrolysis at temperature of 450°C. To increase the performance of the biochar in absorbing H₂S, hydrogel biochar was produced by performing polymerization. The characteristics analysis in elemental analysis, functional group, surface area, pore volume and pore size had been done on rice husk, biochar and hydrogel biochar. Then, the absorption of H₂S with sorbent weight as parameter has been performed on biochar and hydrogel biochar. The result of H₂S absorption by biochar showed that the mass of H₂S per weight of sorbent increase as the sorbent weight increase. However, the hydrogel biochar unable to perform the result that being predicted.